2020
DOI: 10.1016/j.najef.2020.101162
|View full text |Cite
|
Sign up to set email alerts
|

Tornado activity, house prices, and stock returns

Abstract: In this paper we investigate the effects of tornado activity on house prices and stock returns in the US. First, using geo-referenced and metropolitan statistical area (MSA)-level data, we find tornado activity to be responsible for a significant drop in house prices. Spillover tornado effects between adjacent MSAs are also detected. Furthermore, our granular analysis provides evidence of tornadoes having a negative impact on stock returns. However, only two sectors seem to contribute to such a negative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Our objective is to forecast stock return volatility of an important emerging market economy, namely South Africa, using the informational content of rare disaster risk, over the monthly period from February 1910 to February 2023. In line with the burgeoning literature on climate finance, we use changes in the temperature anomaly and its volatility as an empirical proxy of the theoretical concept of rare disaster risk, as in the advanced financial market movements-based research by [11][12][13][14][15], given that climate change poses a large aggregate risk to the overall macroeconomy and the global financial system due to the associated occurrences of rare disasters originating from physical risks involved with global warming and climate change [16][17][18]. To this end, we study data that span more than a century because climate change is a slow-moving process and its effects have tended to aggravate over time as economies have become more and more industrialized.…”
Section: Introductionmentioning
confidence: 99%
“…Our objective is to forecast stock return volatility of an important emerging market economy, namely South Africa, using the informational content of rare disaster risk, over the monthly period from February 1910 to February 2023. In line with the burgeoning literature on climate finance, we use changes in the temperature anomaly and its volatility as an empirical proxy of the theoretical concept of rare disaster risk, as in the advanced financial market movements-based research by [11][12][13][14][15], given that climate change poses a large aggregate risk to the overall macroeconomy and the global financial system due to the associated occurrences of rare disasters originating from physical risks involved with global warming and climate change [16][17][18]. To this end, we study data that span more than a century because climate change is a slow-moving process and its effects have tended to aggravate over time as economies have become more and more industrialized.…”
Section: Introductionmentioning
confidence: 99%
“…Against the backdrop of empirical evidence of the impact of climate risks on output growth, provided primarily at the aggregate individual or a panel of countries, we aim to extend this line of research in two novel ways: First, we analyse, for the first time, the effects of both growth in temperature and its volatility on the economic activity of a panel of 50 states of the United States (US), over the monthly period of 1984 to 2019. 2 Second, and again for 2 The only other somewhat related paper is that of Donadelli et al (2020), wherein the authors, inter alia, reported negative impacts of tornado activity on the four census regions (Northeast, Midwest, South and West) of the US, but based on annual data. Understandably, a high-frequency analysis like that of ours is more valuable to policymakers in designing responses to mitigating climate risks in a timely-manner than those derived from annual data-centric findings.…”
Section: Introductionmentioning
confidence: 99%